2016
DOI: 10.2337/db15-1418
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Encoding Bone Marrow Terminates Islet-Directed Memory CD8+ T-Cell Responses to Alleviate Islet Transplant Rejection

Abstract: Islet-specific memory T cells arise early in type 1 diabetes (T1D), persist for long periods, perpetuate disease, and are rapidly reactivated by islet transplantation. As memory T cells are poorly controlled by "conventional" therapies, memory T cell-mediated attack is a substantial challenge in islet transplantation, and this will extend to application of personalized approaches using stem cell-derived replacement b-cells. New approaches are required to limit memory autoimmune attack of transplanted islets or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…These observations indicate ‘adaptive tuning’ of residual undeleted insulin‐specific CD8 + Tmem to the proinsulin expressed in PI‐Tg recipients. An unexpected finding was that CD5, which is an indicator of antigen‐sensing 39 and upregulated by tolerant T cells in many settings, 26 , 40 was not upregulated by inactivated G9 Tmem in PI‐Tg recipients. This could perhaps reflect altered regulation of CD5 in Tmem, particularly as CD5 expression was reduced during in vitro Tm differentiation ().…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations indicate ‘adaptive tuning’ of residual undeleted insulin‐specific CD8 + Tmem to the proinsulin expressed in PI‐Tg recipients. An unexpected finding was that CD5, which is an indicator of antigen‐sensing 39 and upregulated by tolerant T cells in many settings, 26 , 40 was not upregulated by inactivated G9 Tmem in PI‐Tg recipients. This could perhaps reflect altered regulation of CD5 in Tmem, particularly as CD5 expression was reduced during in vitro Tm differentiation ().…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, transfer of genetically modified haematopoietic stem cells shows that gene therapy has the potential to be an effective treatment 26,44,45 and this is capable of preventing recurrent autoimmune attack of transplanted islets. 26 Here we found no inflammatory infiltrates in pancreatic islets of PI-Tg recipients of G9 Tmem, even after immunisation (e.g. Figure 4) or CTL (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective engraftment and establishment of hematopoiesis by the transferred HSPC is required for the continued genesis of antigen-expressing APC in order to generate a long-lived tolerogenic state in recipients. While, thymic mechanisms might prevent emergence of de novo antigen-specific T cells, the antigen-expressing APC that develop inactivate existing populations of antigen-specific T cells through peripheral tolerance mechanisms (27), and this has been demonstrated to extend to pathogenic CD8 + T cells (31). Whereas others have shown that expression of allergen by BM-derived cells can induce T cell and B cell tolerance in recipients of gene-engineered BM cells, this has been tested only under harsh, fully immunoablative conditions (43) where central tolerance mechanisms that influence development of naive lymphocyte populations may predominate.…”
Section: Discussionmentioning
confidence: 99%